Construction of unique SCF3-containing building blocks via allylic alkylation of Morita–Baylis–Hillman adducts. Issue 11 (2nd March 2020) - Halder, Priyanka; Pol, Mahesh D.; Ahire, Milind M.; Mhaske, Santosh B.
Abstract : Lewis base-catalyzed allylic alkylation of MBH adducts with α-SCF3 ketones has been demonstrated to provide an efficient access to a series of highly functionalized scaffolds featuring trifluoromethanesulfinyl motif on a stereogenic carbon. Abstract : Lewis base-catalyzed allylic alkylation of Morita–Baylis–Hillman adducts with α-SCF3 ketones has been demonstrated. The developed strategy provides efficient access to a series of highly functionalized scaffolds featuring trifluoromethanesufinyl motif on a stereogenic carbon.